Pengaruh Beban Kerja dan Stress Kerja Terhadap Turnover Intention - Ardina Anjani; R. Deni Muhammad Danial; Faizal Mulia Z (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of workload and work stress on turnover intention at PT. Sumber Alfaria Trijaya as a trading company for various products. The research method used is a quantitative method with an associative approach. Data was collected through a questionnaire distributed to PT employees. Source Alfaria Trijaya. The population in this study was all 66 employees using saturated sampling. The research analysis technique uses validity and reliability tests, classical assumption tests, and multiple linear regression which function to prove the research hypothesis. Based on the data obtained from the analysis results, it shows that the correlation analysis in the research has a strong and very high value. The regression coefficient for workload is 0,433 then the regression coefficient for work stress is 0,520. The results of the F hypothesis test show that the calculated f value is greater than table f. Meanwhile, the results of the T test show that the calculated t is greater than the t table. So it can be concluded that the workload variable has a negative and significant effect on turnover intention, and the work stress variable has a positive and significant effect on turnover intention.